PEMANFAATAN PADUAN AL (SCRAP) SEBAGAI BUCKET TURBIN PELTON MENGGUNAKAN METODE PENGECORAN EVAPORATIVE - Ali Ridho; Rudi Siswanto (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Aluminum rongsok (scrap) is widely produced from households, IKM, offices, factories and so on in South Kalimantan. Along this time Al rongsok only collected by the collectors and then sold to the company smelting (in Java). Al rongsok can be recycled and used as a cast product, so potentially produce components, one of which is Pelton turbine bucket. This research aims to; (1) to create a prototype Pelton water-type bucket turbine using styrofoam pattern (2) to know the micro structure, hardness, tensile strength, and impact strength. The furnace for smelting uses a krasibel type furnace with charcoal wood fuel. Material for casting used Al alloy (scrap). The evaporative casting method is to use styrofoam as a molding pattern that is dumped in the printed sand. This method will produce castings that match the pattern / model formed. Melting is done by melting the Al in the kitchen krusibel then poured on the variation of casting temperature 650, 670, 690 and 710 oC. The casting results are then tested for mechanical properties (micro structure, hardness, tensile strength, and impact strength). The test results concluded, Al alloy (scrap) can be utilized and developed as prototype of cross flow water turbine blade / bucket using evaporative casting method. the higher the temperture of the hypereutectic Si structure is present between the dendrite Al of thin short flakes into thick, long bits. At temperatures above 650 oC, the value of hardness decreases with the increase of pouring temperature, while tensile stress decreases with increasing of pouring temperature. Impetus has been declining as the pouring temperature increases.Keywords: Evaporative casting, Al (Scrap), physical-mechanical properties, Pelton turbine bucket